A capacitação de servidores técnico-administrativos: desenvolvendo na UFPA competências por meio do conhecimento - SERIQUE, Maria Rosangila Xavier (Universidade Federal do Pará, 2012)
To meet the challenges of the new millennium, institutions, organizations and the general world of work should be more concerned with people, investing, especially in well-being, personal fulfillment and professional, through training and skills, and knowledge considered the driving force of development. This study aims to investigate whether the general training of technical and administrative staff (TA) of the Federal University of Pará (UFPA) who carried out the courses of specialization in Strategic Management and Personnel Management, in the period 2002 to 2004, the UFPA, Campus Belém, contributed to improving the performance of their units through the knowledge acquired. From the research methodology literature and field research, has been the presentation of the theoretical foundation about the subject under study, based on a qualitative approach, using data collection, documents and interviews. Had managers as informants Dean of Planning (PROPLAN) and Dean of development and personnel management (PROGEP) performing during the research period and still, fifteen servers graduates of the specialization. For interpretation of the data used was content analysis, allowing a better interpretation of the speech of the interviewees, the result indicates that those courses were formed in the pressing need for the framework of technical and administrative staff, from a process of continuous education better performance of work activities, and greater satisfaction and motivation to work, concluding that the UFPA, as a center to provide public educational services for the citizen, should give priority to a policy of continued effective and professional valuation your server, noting that knowledge is an essential tool in human resource policy of the servers to generate power in order that the UFPA own benefit as n and the professionalization and enhancement of the server as a result have shown greater efficiency in the delivery services targeted to society, first objective of governmental institutions.